Salivary Cortisol Concentration Is an Objective Measure of the Physiological Response to Loud Music - Robert Tomljenović; Andro Košec; Livije Kalogjera; Ivana Ćelap; Domagoj Marijančević; Davor Vagić (Audiology Research)
Purpose: This study examines the potential associations between salivary cortisol concentrations and subjective stress test scores in healthy individuals subjected to sound-related, psychological, and physical stressors. Methods: This study employed a single-center observational cross-sectional design, with a sample size of 36 subjects recruited from a tertiary referral audiology center. Between 2023 and 2024, the study recruited subjects with normal hearing, baseline salivary cortisol levels, and subjective stress levels. The participants were requested to complete an STAI-Y1 questionnaire and provide salivary cortisol samples before and following exposure to sound-related, psychological, and physical stress tests. Results: Exposure to psychological and physical stressors significantly increased STAI-Y1 scores (Friedman’s test, χ2 = 57.118, df = 2, p = 0.377). This increase was greater than that observed in response to loud, favorite music (Friedman’s test, χ2 = 57.118, df = 2, p < 0.0001). The salivary cortisol concentration significantly increased in all three provocation tests (Friedman’s test, χ2 = 95.264, df = 5, p < 0.0001). Furthermore, there is no significant difference in salivary cortisol concentrations between the three pre-test and post-test measurement intervals, indicating a comparable stress-inducing pattern regardless of the nature of the stimulus (Friedman’s test, χ2 = 95.264, df = 5, p > 0.05). Conclusions: Exposure to loud favorite music increases salivary cortisol concentrations, as does acute physical and psychological stress. Interestingly, unlike psychological and physical stress, loud music was not objectively perceived as stress, which may mask the physiological signs of stress, potentially increasing the risk of both acute and chronic stress-related health outcomes.